Timber booms and institutional breakdown in southeast Asia - Ross, Michael Lewin 1961- (Political economy of institutions and decisions, 2001)
Scholars have long studied how institutions emerge and become stable. But why do institutions sometimes break down? In this book, Michael L. Ross explores the breakdown of the institutions that govern natural resource exports in developing states. He shows that these institutions often break down when states receive positive trade shocks - unanticipated windfalls. Drawing on the theory of rent-seeking, he suggests that these institutions succumb to a problem he calls 'rent-seizing' - the predatory behavior of politicians who seek to supply rent to others, and who purposefully dismantle institutions that restrain them. Using case studies of timber booms in Indonesia, Malaysia and the Philippines, he shows how windfalls tend to trigger rent-seizing activities that may have disastrous consequences for state institutions, and for the government of natural resources. More generally, he shows how institutions can collapse when they have become endogenous to any rent-seeking process